Avaliação dos mecanismos de endurecimentoda liga AISI 300M submetida a diferentes ciclos de transformações martensíticas - Prado, Camila Cristina Silva do [UNESP] (2015)
The AISI 300M steel, known as a ultra-high strength steel, was developed as an evolution of the SAE 4340 steel, in order to acquire a better tenacity and weldability in applications that demand better mechanical properties and quenching facility. Nowadays, its use is directed for the aerospace segment, being it applied in satellite launch vehicle (VLS) parts, in some probing vehicles that are part of the Brazilian Space Program and in the production of its propellant envelopes (propellant). The aim of this paper is to attribute better features to the use of this steel, through low cost procedures and equipment. For this purpose, martensitic transformation cycles were made to refine microstructures. The martensitic transformation cycles were made in a resistive mufla oven, aiming at nucleation of new grains in each new martensitic transformation. To analyze the results obtained, a correlative microscopy technique was used, which consists in the association of optical microscopy technique and electronic scanning with the purpose of investigating the same subject. Through this technique it was possible to check and identify the structures in an optical microscopy. Mechanical tests, such as tensile and hardness tests, besides a microstructural analysis and X-ray diffraction, were made in order to improve the results analysis. Cycles with heating to 900ºC and water quenching were considered the best condition of grain refining per martensitic transformation cycle